HRM in the Age of Gen Z: Balancing Flexibility, Well-Being, and Productivity - Muchtar, Abdul Haris (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
The rise of Generation Z in the global workforce has brought significant implications for human resource management (HRM), requiring organizations to adapt their strategies to new expectations regarding flexibility, well-being, and productivity. This study employs a qualitative approach with a library research method to examine how HRM can effectively respond to the evolving demands of Gen Z employees. The normative expectation is that HRM should balance employee autonomy with organizational accountability, safeguard well-being as a strategic priority, and redefine productivity in ways that reflect creativity, adaptability, and collaborative outcomes. However, empirical evidence suggests that many organizations remain dependent on traditional HRM frameworks that emphasize rigid structures, quantitative outputs, and reactive approaches to employee well-being, leading to a mismatch between organizational practices and generational values. A review of contemporary literature reveals that Gen Z considers flexibility a non-negotiable condition of employment, while mental health, inclusivity, and purpose-driven work are central to their engagement. At the same time, studies highlight that productivity can no longer be measured solely through efficiency metrics but must encompass qualitative contributions. Despite this growing recognition, there remains a gap in integrating these three dimensions into a unified HRM framework. This research argues that flexibility, well-being, and productivity are interdependent factors that must be addressed collectively to avoid counterproductive outcomes. The findings suggest that organizations should redesign HRM practices to create environments where Gen Z employees can thrive without compromising organizational effectiveness.